Thrombosis risk of Alport syndrome patients: evaluation of cardiological, clinical, biochemical, genetic and possible causes of inherited thrombophilia and identification of a novel COL4A3 variant. Issue 4 (June 2020) - Eroz, Recep; Damar, İbrahim H. and Kılıçaslan, Onder
Abstract : N/A: To evaluate cases with Alport syndrome for laboratory, radiological, ophthalmological, auditory tests, cardiological and inherited thrombophilia risk. Laboratory findings, abdominal and urinary ultrasonography, ophthalmological and auditory tests and cardiological examination of 21 Alport syndrome suspicious cases were performed. Also, collagen type IV alpha three chain ( COL4A3 ) gene, four chain ( COL4A4 ) gene and five chain ( COL4A5 ) genes were sequenced by next-generation sequencing system. In addition, possible causes of inherited thrombophilia were evaluated. A novel (c.2806C>T/p.Gln936Ter) variation in COL4A3 gene was detected in three cases. Also c.221G>A/p.Arg74Gln variation in COL4A5 gene of two cases, c.4421C>T/p.Thr1474Met variation in COL4A4 gene of one case, c.665C>T/p.Pro222Leu variation in COL4A4 gene of one case and compound heterozygous c.4421C>T/(p.Thr1474Met) and c.665C>T/p.Pro222Leu variation in COL4A4 gene of one case were detected. Although 10 (47.6%) cases had microscopic hematuria, six (28.6%) cases had macroscopic hematuria, but there were not hematuria in five (23.8%) of cases. Three cases with variation carrier in COL4A genes and one case without variation carrier had vision problem. Also, one case with variation carrier in COL4A gene had hearing loss. All cases with variation carrier in COL4A genes exclude one had at least one cardiac problems. Also, all cases with variation carrier in COL4A genes had possible causes of inherited thrombophilia risk. In addition to developing risk of progressive kidney failure, sensorineural hearing loss and ocular abnormalities, Alport syndrome cases may have increasing cardiac problems and possible causes of inherited thrombophilia risk. Therefore, these cases should be regularly evaluated and followed for cardiac problems and inherited thrombophilia risk.